2015
DOI: 10.3823/1794
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Of Stroke Risk Factors And Warning Signs And Attitude To Acute Stroke

Abstract: Background: Stroke is a leading cause of death and disability worldwide. Knowledge of stroke risk factors and warning signs might improve its prevention and ensure prompt activation of emergency medical services and access to thrombolysis. Educational campaigns have been held in Portugal though its impact on knowledge of medical patients has not been assessed. Methods:A cross-sectional observational study was performed to medical outpatients, through an interview. Main objectives were to assess the extent of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 60 publications
4
16
7
1
Order By: Relevance
“…One-sided weakness was identified as a common warning sign of stroke in similar studies. 5,8,15,17,19, Our study did not show any significant association between stroke awareness and gender. Few studies had reported gender bias in stroke awareness.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…One-sided weakness was identified as a common warning sign of stroke in similar studies. 5,8,15,17,19, Our study did not show any significant association between stroke awareness and gender. Few studies had reported gender bias in stroke awareness.…”
Section: Discussioncontrasting
confidence: 64%
“…Similar awareness on risk factors of stroke was observed in hospital based studies done in New Delhi 14 and Lisbon. 15 Subjects who did not identify even one risk factor ranged from 6% to 45% in various studies from across the world. [16][17][18][19][20] The risk factor identified by most in the present study was hypertension (94%); followed by lack of exercise (82.5%), smoking (81.5%), diabetes mellitus (75%) and stress (73%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations